Bahasa Inggris: English - Novita, Dien; Kusumah, Cita Mustika (JELA (Journal of English Language Teaching, Literature and Applied Linguistics), 2025)
This study examines the editorial text "Corruption, not a Priority?" from the Jakarta Post on March 17, 2015. This research aims to identify appraisal system devices in the text and to determine the reader's location within the text. Martin and White's (2005) Appraisal Theory was used to assess the text. The data were analyzed using a descriptive qualitative method, with clauses as the unit of analysis. The results demonstrate that the editorial text has three subsystems: attitude, engagement, and graduation. Appreciation systems account for the majority of attitude systems (31 categories). Monoglosses account for 46% of the components in engagement systems. The graduating systems are dominated by 38 systems of concentration. The writer persuades readers to agree with his or her opinions and worries about the subject. He or she makes unfavorable judgments on the appreciation systems, which are common among attitude systems.